THE EFFECT OF ZIG ZAG RUN TRAINING ON THE AGILITY OF FOOTBALL PLAYERS IN SSB WONER - Hafiz, Abdul Hafiz; Ramadi; Agus Prima Aspa (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2023)
The problem in research is the lack of agility that students have at SSB Woner. the purpose of this study was to determine the effect of the zig zag run exercise on the agility of SSB Woner students. The population in this study were all students aged 15 years using a total sampling technique, amounting to 15 students. This type of research is, using a one-group pre-test-post-test design. From the results of this study it can be concluded that the average pre-test was 19.13 and the post-test was 17.05, based on the normality test LoMax pretest was 0.1329 <L table 0.22, and LoMax posttest was 0.1224 <L table 0.22 is said to be normal. based on statistical analysis of the t test, the difference value is 2.01 and produces a tcount of 15.461 and a ttable of 1.761. Means tcount > ttable. It can be concluded that the zigzag run exercise (X) has an influence on agility (Y) on soccer players in SSB Woner Keyword: zig zag run training, agility, soccer